POLITENESS STRATEGIES USED BY PEDICAB DRIVERS TO FOREIGN TOURISTS IN MALIOBORO STREET - Setyawan, Agustinus Hary; Binawan, Heribertus; Nugraeni, Nugraeni (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This study discusses the use of English used by pedicab drivers in the Malioboro tourist area as a means of communication with foreign tourists to portray and improve the quality of English-speaking services in the future. By bringing out the element of politeness in communicating, people can further strengthen their social relations, both can respect each other's self-image. Unique informal learning from direct conversations with foreign tourists produces speech variations in English that are unique and different from standard English rules. This study is a qualitative descriptive study with conversational analysis that aims to describe the linguistic phenomena in the English variation of pedicab drivers on aspects of politeness strategies. Pedicab drivers in tourist locations utilize politeness strategies to create communications when face-threatening acts are unavoidable or deliberate in order to preserve the hearer's positive and negative face. In the interactions between pedicab drivers and international tourists, 15 data on positive politeness strategies and 14 data on negative politeness strategies were identified. The data analysis provided is taken from the representative data for each strategy. The dominant sub-strategy from the positive politeness strategy is "Notice, Attend to H (his Interest, Wants, Needs, Goods)," while the dominant sub-strategy from the negative politeness strategy is "Apologize."